Indications and Limitations of Sirolimus in the Treatment of Vascular Anomalies—Insights From a Retrospective Case Series - Karastaneva, Anna; Gasparella, Paolo; Tschauner, Sebastian; Crazzolara, Roman; Kropshofer, Gabriele; Modl, Manfred; Pfleger, Andreas; Burmas, Ante; Pocivalnik, Mirjam; Ulreich, Raphael; Zenz, Werner; Schwinger, Wolfgang; et al. (Frontiers in Pediatrics, 2022)
Background. Despite recent developments, the role of sirolimus in the heterogeneous spectrum of vascular anomalies is yet to be defined, in terms of indication, dosage, and therapy duration, recognizing both its potential and limitations. Methods. We retrospectively analyzed 16 children with vascular anomalies treated with sirolimus in two pediatric centers between 2014 and 2020 (male: n=7, the median age at diagnosis: 4.6 months [range, 0-281.4]). In addition, repetitive volumetric analyses of the vascular anomalies were performed when possible (11 cases). Results. Ten patients were diagnosed with vascular malformations and 6 with vascular tumors. The mean therapy duration was 27.2 months (range, 3.5-65). The mean sirolimus level was 8.52 ng/ml (range, 5.38-12.88). All patients except one with central conducting lymphatic anomaly responded to sirolimus, with the most noticeable volume reduction in the first 4-6 months. Additional administration of vincristine was needed in five patients with kaposiform hemangioendothelioma and yielded a response, even in cases, refractory to sirolimus monotherapy. As a single agent, sirolimus led to impressive improvement in a patient with another vascular tumor - advanced epithelioid hemangioendothelioma. Complicated vascular malformations required long-term sirolimus therapy. Side effects of sirolimus included mucositis and laboratory abnormalities. No major infectious episodes were recorded. An infant with COVID-19, diagnosed while on sirolimus therapy, presented with a mild course. Conclusion. In the current series, we reported limitations of sirolimus as monotherapy, addressing the need to redefine its indications, explore combination regimens and multimodal treatment strategies. Tools for objective evaluation of response trends over time could serve as a basis for the establishment of future therapeutic algorithms.